2006
DOI: 10.1021/bi061684b
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Multi-Enzyme Complexes:  The Case of Tryptophan Synthase

Abstract: The prototypical tryptophan synthase is a stable heterotetrameric alpha-betabeta-alpha complex. The constituting TrpA and TrpB1 subunits, which are encoded by neighboring genes in the trp operon, activate each other in a bi-directional manner. Recently, a novel class of TrpB2 proteins has been identified, whose members contain additional amino acids that might sterically prevent complex formation with TrpA. To test this hypothesis, we characterized the TrpA and TrpB proteins from Sulfolobus solfataricus. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 56 publications
1
42
0
Order By: Relevance
“…1 It has been shown that the ssTrpB2i enzyme from Sulfolobus solfataricus forms with ssTrpA a transient, ligand-dependent tryptophan synthase complex having αββ stoichiometry. 8,9 This finding indicates a functional equivalence of TrpB2i and TrpB1 in vivo. In contrast, all TrpB2o and TrpB2a enzymes characterized to date do not interact with TrpA.…”
mentioning
confidence: 62%
“…1 It has been shown that the ssTrpB2i enzyme from Sulfolobus solfataricus forms with ssTrpA a transient, ligand-dependent tryptophan synthase complex having αββ stoichiometry. 8,9 This finding indicates a functional equivalence of TrpB2i and TrpB1 in vivo. In contrast, all TrpB2o and TrpB2a enzymes characterized to date do not interact with TrpA.…”
mentioning
confidence: 62%
“…Moreover, activity titrations have shown that the affinity of sTrpB2i for sTrpA is increased by 2 orders in the presence of L-serine (18). At 60°C, values for K M Ser of 7 mM (Supporting Information Figure S1B) and 40 mM (18) have been determined, independent of the presence of sTrpA. These values are 2 orders of magnitude higher than the intracellular concentration of L-serine found in E. coli (59).…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, the results for the TS from S. solfataricus indicate that the interaction of sTrpA and sTrpB2i is transient and depending on the presence of TrpA and TrpB ligands and that the affinity between the subunits is relatively weak (Table 1). In activity titrations, where catalysis by sTrpA was measured as a function of added sTrpB2i, apparent dissociation constants of 280 nM (with L-serine) and 22 μM (without L-serine) were determined (18). After having stabilized the complex by the ligands GP and L-serine, we now quantified subunit affinity and stoichiometry in the absence of catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…This enzyme has attracted a great deal of attention and been extensively reviewed as the one of the first enzymes to be discovered that catalyzes two distinct reactions at independent active sites (in the a-and b-domains) that are connected via an internal tunnel [274]. This was the first well-documented example of substrate channeling in amino acid biosynthesis.…”
Section: Tryptophan Biosynthesismentioning
confidence: 99%